The development of the popular scientific books on butterflies in the mangrove Sungai Bakau on student’s critical thinking skills - Devy Dwi Rahayu; Dharmono Dharmono; Rusmiati Rusmiati (Master Program of Biology Education, Universitas Lambung Mangkurat, 2022)
Innovative and easy-to-understand learning resources for students that contain materials based on local potentials that can improve students' critical thinking skills are still limited. This study aims to describe the validity, practicality, and effectiveness of popular scientific books on butterflies in the mangrove forest area of Sungai Bakau Village on students' critical thinking skills. Step by step of development includes self evaluation, expert trials, individual trials, small group tests, and field tests. Research subjects are 3 bioscientists, 3 students for individual trials and for small group tests, and 15 students for field Innovative learning resources that contain materials tests. The study shows that the popular scientific books that had been developed are highly valid for 96.3%, while individual testing discovered an excellent value to 88.1%. Popular scientific books are practical because students’ responses to 94.7% with highly practicable criteria, the results of the publication of popular scientific books averaged 88.89% by excellent criteria. Popular scientific books that had been developed can be regarded as effective due to increment in students' learning outcomes with an average value to 88.30%. This is categorized as a very good criterion, especially supported by the increment in critical thinking skills up to 0.71 with high criteria.Abstrak Sumber belajar yang inovatif dan mudah dipahami mahasiswa yang memuat materi berbasis potensi lokal dapat meningkatkan keterampilan berpikir kritis mahasiswa masih terbatas. Penelitian ini bertujuan mendeskripsikan validitas, kepraktisan, dan keefektifan buku ilmiah populer kupu-kupu di kawasan hutan mangrove Desa Sungai Bakau terhadap keterampilan berpikir kritis mahasiswa. Tahap-tahap pengembangan menggunakan evaluasi formatif Tessmer yang meliputi evaluasi diri, uji pakar, uji perorangan, uji kelompok kecil, dan uji lapangan. Subjek penelitian adalah 3 pakar pembelajaran biologi, 3 mahasiswa untuk uji perorangan dan uji kelompok kecil dan 15 mahasiswa untuk uji lapangan. Hasil penelitian menunjukan BIP yang telah dikembangkan dinyatakan sangat valid dengan nilai 96,3%, sedangkan berdasarkan uji perorangan BIP ini dinyatakan sangat baik dengan nilai 88,1%. BIP dinyatakan praktis karena hasil respon mahasiswa sebesar 94,7% dengan kriteria sangat praktis, hasil keterlaksanaan BIP rata-rata 88,89% denga kriteria sangat baik. BIP yang dikembangkan dinyatakan efektif karena peningkatan hasil belajar mahasiswa dengan rata-rata nilai 88,30% dengan kriteria sangat baik dan peningkatan keterampilan berpikir kritis sebesar 0,71 dengan kriteria tinggi.